Du port du turban à l’arbitrage religieux : les limites du multiculturalisme canadien comme projet de société - Sandrine Tolazzi (Anglophonia)
Since it was adopted as government policy in 1971, Canadian multiculturalism has always tried to steer between the need to respect the different communities living in the country and the necessity of maintaining unity. Thus, it is both a policy of recognition which aims at promoting difference and a policy of integration at the heart of a societal project based on developing a pan-Canadian identity. However, in the post-9/11 context, the fragile balance between these two aspects of the aforementioned policy seems to be increasingly threatened. While some may question its principles on the account that they are a menace to an "ideal" homogeneity, others would like it to be further enforced even though it might increase differences between the groups. Therefore, multiculturalism is being faced with new challenges, among which the debate on the possibility of using Islamic law in the arbitration of family matters is only one example. Drawing from such examples, this article comments on the limits of multiculturalism as an instrument of social cohesion and shows how the flexibility of the policy makes it possible to deal with these challenges